Gold Nanoparticle Platforms Enabling Targeted Cancer Imaging and Treatment - Jin, Zishan (Transactions on Environment, Energy and Earth Sciences, 2026)
Gold nanoparticles (AuNPs) combine a high atomic number with tunable surface plasmon resonance, enabling both diagnostic and therapeutic applications in cancer. Their strong X-ray attenuation provides excellent contrast for computed tomography, while near-infrared (NIR) plasmonic absorption allows efficient photothermal conversion for tumour ablation. Versatile surface chemistry supports precise control over size, shape and ligand functionalisation, which governs biodistribution, cellular uptake and therapeutic performance. Clinical pilot studies have shown promising outcomes in focal tumour imaging and minimally invasive photothermal therapy (PTT), and nucleic acid–grafted AuNPs have demonstrated the ability to cross the blood–brain barrier for gene regulation. Despite these advances, key translational challenges remain, including the need for predictable long-term clearance, scalable synthesis with consistent quality, and well-defined regulatory standards. This review summarises current synthesis strategies, critical physicochemical properties and representative biomedical applications of AuNPs, and highlights design principles that will be essential for achieving safe and reproducible clinical deployment.